2007
DOI: 10.1002/anie.200702086
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Formation of Allylic Amines with N‐Substituted Quaternary Stereocenters by PdII‐Catalyzed Aza‐Claisen Rearrangements

Abstract: Dedicated to Professor Dieter Seebach on the occasion of his 70th birthdayEnantiomerically pure allylic amines are valuable building blocks, as they possess two highly versatile functional groups. Two widely used methods for their preparation are the transition-metal-catalyzed allylic substitution [1] and the azaClaisen rearrangement of trihaloacetimidates (Overman rearrangement).[2] A longstanding problem is the catalytic enantioselective formation of quaternary stereocenters by either of these methodologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Supporting Information for Alexy,Yoritate,Wright and Stoltz SI11 128.3,116.2 (q,J = 289.7 Hz),115.3,115.1,113.8,113.3,68.0,55.5,41.4,32.2,30.5,27.1,20.7;19 F NMR (282 MHz,; IR (Neat film, NaCl) 3443,2936,1698,1509,1252,1201,1179,1154,1032,970,834 4,132.8,132.6,129.2,128.4,125.4,116.2 (q,J = 289.8 Hz),113.8,113.3,68.0,55.5,41.5,30.4,20.8;19 5,132.7,132.4,131.5,128.2,127.8,124.5,123.5,116.2 (q,J = 289.7 Hz),113.9,113.5,88.9,80.8,…”
Section: Mementioning
confidence: 99%
See 1 more Smart Citation
“…Supporting Information for Alexy,Yoritate,Wright and Stoltz SI11 128.3,116.2 (q,J = 289.7 Hz),115.3,115.1,113.8,113.3,68.0,55.5,41.4,32.2,30.5,27.1,20.7;19 F NMR (282 MHz,; IR (Neat film, NaCl) 3443,2936,1698,1509,1252,1201,1179,1154,1032,970,834 4,132.8,132.6,129.2,128.4,125.4,116.2 (q,J = 289.8 Hz),113.8,113.3,68.0,55.5,41.5,30.4,20.8;19 5,132.7,132.4,131.5,128.2,127.8,124.5,123.5,116.2 (q,J = 289.7 Hz),113.9,113.5,88.9,80.8,…”
Section: Mementioning
confidence: 99%
“…= 15.9, 4.5, 1.8 Hz, 1H), 2.51 -2.34 (m, 2H), 2.33 -1.85 (m, 8H), 1.85 -1.58 (m, 3H);13 C NMR (100 MHz, Chloroform-d) δ 205.0, 160.4, 157.3 (q, J = 35.1 Hz), 140.9, 132 4,. 131.8, 128.5, 128.1, 127.7, 126.2, 122.3, 116.3 (q, J = 288.3 Hz), 114.0, 113.9, 72.0, 55.6, 40.1, 36.5, …”
mentioning
confidence: 99%
“…Included in the range of substrates transformed were Z-configured trifluoroacetimidates containing an a-branched substituent (Z)-117, (R ¼ i-Pr), and the methodology has been successfully extended to a give a range of highly scalemic functionalized allylic amine building blocks [35b]. The use of trifluoroacetimidate substrates has been extended to the asymmetric synthesis of quaternary stereogenic centers with the monopalladocyclic FIP-catalyst precursor (S p ) 2 -119 (Scheme 12.34) [77]. The addition of 3 equiv (with respect to (S p ) 2 -119) of 1,8-bis(dimethylamino)naphthylene as an acid scavenger largely suppresses the acid-catalyzed elimination of trifluoroacetamide which is otherwise a significant problem with the 3,3-disubstituted substrates 122.…”
Section: Allylic Imidate Rearrangementmentioning
confidence: 99%
“…Cui, Wu and their coworkers showed that the ferrocenylimidazoline palladacycles were efficient catalysts for the Suzuki-Miyaura cross-coupling reaction, even allowing the use of aryl chlorides [12,13] . In addition, chiral ferrocenyl imidazolines have also been synthesized by Peters and coworkers [14][15][16][17][18][19][20][21] . They found the planar chiral palladacycles derived from the above chiral ferrocenyl imidazolines were able to catalyze the aza-Claisen rearrangements with up to excellent enantioselectivities [21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%